The ice at the end of the world : an epic journey into Greenland's buried past and our perilous future - Gertner, Jon (Random House, 2019)
"Greenland: remote, mysterious, ice-covered rock, population 56,000, in the middle of the North Atlantic. Why do we care so much about it? Because locked within the the vast and frozen "white desert"--the nickname early explorers gave it--that covers eighty percent of the land are some of the most profound secrets of our planet--clues about where we've been, and where we might be headed. And now, with the ice sheet melting at an unprecedented rate, we are able, for the first time, to understand the story that lies within it, and what it can tell us about our future. In The Ice at the End of the World, Jon Gertner reconstructs in vivid, thrilling detail the heroic efforts of the scientists and explorers who have visited Greenland over the past 150 years--first on skis, then on sleds, and now, with planes and satellites, utilizing every technological tool available to uncover the secrets in the ice before it's too late. Much as he did with his depiction of solid-state engineers and laser scientists in his bestselling book The Idea Factory, Gertner chronicles the amazing advances, almost unfathomable hardships, technological leaps, and scientific achievements of Arctic researchers with a rich, transporting, deeply intelligent style that melds the compelling stories of a small cast of brilliant and eccentric individuals, with a keen, analytical eye toward what this work means for the rest of us"--